Magnetic resonance imaging of hypoxia in acute stroke compared with fluorine‐18 fluoromisonidazole‐positron emission tomography: A cross‐validation study?. (15th November 2022) - Valable, Samuel; Toutain, Jérôme; Divoux, Didier; Chazalviel, Laurent; Corroyer‐Dulmont, Aurélien; Chakhoyan, Ararat; Guillouet, Stéphane; Bernaudin, Myriam; Barbier, Emmanuel L.; Touzani, Omar
Abstract: Acute ischemic stroke results in an ischemic core surrounded by a tissue at risk, named the penumbra, which is potentially salvageable. One way to differentiate the tissues is to measure the hypoxia status. The purpose of the current study is to correlate the abnormal brain tissue volume derived from magnetic resonance‐based imaging of brain oxygen saturation (St O2 ‐MRI) to the fluorine‐18 fluoromisonidazole ([ 18 F]FMISO) positron emission tomography (PET) volume for hypoxia imaging validation, and to analyze the ability of St O2 ‐MRI to depict the different hypoxic tissue types in the acute phase of stroke. In a pertinent model of stroke in the rat, the volume of tissue with decreased St O2 ‐MRI signal and that with increased uptake of [ 18 F]FMISO were equivalent and correlated (r = 0.706; p  = 0.015). The values of St O2 in the tissue at risk were significantly greater than those quantified in the core of the lesion, and were less than those for healthy tissue (52.3% ± 2.0%; 43.3% ± 1.9%, and 67.9 ± 1.4%, respectively). A threshold value for St O2 of ≈60% as the cut‐off for the identification of the tissue at risk was calculated. Tissue volumes with reduced St O2 ‐MRI correlated with the final lesion (r = 0.964, p  < 0.0001). The findings show that the St O2 ‐MRI approach is sensitive for the detection of hypoxia and for the prediction of the final lesion after stroke. Once validated in acute clinical settings, this approach might be used to enhance the stratification of patients for potential therapeutic interventions. Abstract : In a pertinent model of stroke in the rat, this study compared magnetic resonance‐based imaging of brain oxygen saturation (St O2 ‐MRI) with [ 18 F]FMISO positron emission tomography (PET) for hypoxia imaging and for final stroke lesion prediction. The findings show that the St O2 ‐MRI approach is sensitive for the detection of hypoxia and for the prediction of the final lesion after stroke.